One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Effects of cyanobacteria decomposition on the remobilization and ecological risk of heavy metals in Taihu Lake - Lixiao Ni; Guoxiu Gu; Shiyi Rong; Lingling Hu; Peifang Wang; Shiyin Li; Dandan Li; Xuanyu Liu; Yifei Wang; Kumud Acharya (Environmental Science and Pollution Research, 2019)

Effects of Different Preservation Methods on Physicochemical Property of Marine Pathogen Vibrio anguillarum - Yongxiang Yu; Zheng Zhang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Bin Li; Hao Zhang (Journal of Ocean University of China, 2019)

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Effects of demethylating reagent 5-aza-2′-deoxycytidine on the growth and cephalotaxine production in Cephalotaxus mannii suspension cells - Li-Rong Wei; Wang-Yan Qin; Yong-Cheng Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Engagement of MicroRNA-155 in Exaggerated Oxidative Stress Signal and TRPA1 in the Dorsal Horn of the Spinal Cord and Neuropathic Pain During Chemotherapeutic Oxaliplatin - Fenghua Miao; Rong Wang; Guozhen Cui; Xiaoguang Li; Ting Wang; Xue Li (Neurotoxicity Research, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Convectively Coupled Equatorial Waves Simulated by CAMS-CSM - Lu Wang; Tianjun Zhou; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

Salvianolic acid B protects against ANIT-induced cholestatic liver injury through regulating bile acid transporters and enzymes, and NF-κB/IκB and MAPK pathways - Shengnan Li; Rong Wang; Bin Wu; Yuanyuan Wang; Fuxing Song; Yanqiu Gu; Yongfang Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Numerical Study of Damage Evolution Law of Coal Mine Roadway by Particle Flow Code (PFC) Model - Wan-rong Liu; Xiao Wang; Chuan-ming Li (Geotechnical and Geological Engineering, 2019)

Correction to: Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Geological and geochemical characteristics of the Baogudi Carlin-type gold district (Southwest Guizhou, China) and their geological implications - Songtao Li; Yong Xia; Jianzhong Liu; Zhuojun Xie; Qinping Tan; Yimeng Zhao; Minghua Meng; Lijin Tan; Rong Nie; Zepeng Wang; Guanghong Zhou; Haiyan Guo (Acta Geochimica, 2019)

The potential growth and lipid accumulation in Coccomyxa subellipsoidea triggered by glucose combining with sodium acetate - Zhenyao Wang; Fei Luo; Ziting Wang; Rong Zhou; Yufang Tang; Yuqin Li (World Journal of Microbiology and Biotechnology, 2019)

Influences of immersion bathing in Bacillus velezensis DY-6 on growth performance, non-specific immune enzyme activities and gut microbiota of Apostichopus japonicus - Jinyan Wang; Bin Li; Yingeng Wang; Meijie Liao; Xiaojun Rong; Zheng Zhang (Journal of Oceanology and Limnology, 2019)

Fluorescence “Off-On” Probe for L-Cysteine Detection Based on Nitrogen Doped Carbon Dots - Yin-long Xu; Rong-biao Bai; Cai-yu Qi; Zeng Ren; Xiu-zhi Jia; Zi-gui Kan; Cao-long Li; Fei Wang (Journal of Fluorescence, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

The relationship between surface spectral albedo and soil moisture in an arid Gobi area - Zhenchao Li; Jiaxi Yang; Xiaoqing Gao; Ye Yu; Zhiyuan Zheng; Rong Liu; Chao Wang; Xuhong Hou; Zhigang Wei (Theoretical and Applied Climatology, 2019)

A facile extraction of keratin from pig hair and its properties - Quan-Fang Li; Yufeng He; Rong-Min Wang (Biologia, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Genetic diversity of 324 cultivated tomato germplasm resources using agronomic traits and InDel markers - Lan Jin; Liping Zhao; Yinlei Wang; Rong Zhou; Liuxia Song; Liping Xu; Xia Cui; Ren Li; Wengui Yu; Tongmin Zhao (Euphytica, 2019)

A B-box zinc finger protein, MdBBX10, enhanced salt and drought stresses tolerance in Arabidopsis - Xin Liu; Rong Li; Yaqing Dai; Li Yuan; Qinghua Sun; Shizhong Zhang; Xiaoyun Wang (Plant Molecular Biology, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Chloroplast proteomic analysis of Triticum aestivum L. seedlings responses to low levels of UV-B stress reveals novel molecular mechanism associated with UV-B tolerance - Limei Gao; Xiaofei Wang; Yongfeng Li; Rong Han (Environmental Science and Pollution Research, 2019)

A CkDREB1 gene isolated from Caragana korshinskii Kom. enhances Arabidopsis drought and cold tolerance - Ziyi Zhang; Qi Yang; Chunlin Zhang; Lili Wei; Rong Yue; Guojing Li; Xiaofei Lin; Ruigang Wang (Brazilian Journal of Botany, 2019)

Genomewide analysis of homeobox gene family in apple (Malus domestica Borkh.) and their response to abiotic stress - Rong Li; Hongjuan Ge; Yaqing Dai; Li Yuan; Xin Liu; Qinghua Sun; Xiaoyun Wang (Journal of Genetics, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Effects of the arterial radius and the center-line velocity on the conductivity and electrical impedance of pulsatile flow in the human common carotid artery - Hua Shen; Siqi Li; Yu Wang; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2019)

The response of metabolically active Clostridium community to initial pH shift is closely correlated with microbial Fe(III) reduction in flooded paddy soils - Lina Li; Zhi Qu; Baoli Wang; Rong Jia; Dong Qu (Journal of Soils and Sediments, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.